(untitled) (مجلة الواحات للبحوث والدراسات, 2025)
Imam Abū Alʻbaaās Almaqaary was famous for his many and varied journeys from his birthplace in Tlemcen to the Far Maghreb and then to the Levant as a teacher and author. He also had a prominent role in the scientific and intellectual movement in the Hijaz by building bridges of communication between the Maghreb and the Arab Levant, as he is considered a messenger of sciences and knowledge and a link of communication, intellectual, and scientific exchange. This is what we are trying to highlight in the main points of this research paper: First: Almaqaary and his presence in Hijaz. Second: Almaqaary’s scientific legacy in Hijaz. The descriptive analytical approach was adopted, through collecting, describing, analyzing, and extracting the scientific data related to it. The study concluded that Abū Alʻbaaās Almaqaary’s move to the Hijaz had a positive impact, due to the high status he enjoyed among scholars and politicians, as he left his mark in the field of teaching and writing, while maintaining his belief, approach, and thought. Keywords: Abū Alʻbaaās Almaqaary, scientific, link, the Islamic West, Hijaz.